Kontribusi Model Pembelajaran Web Centric Cource dan Self-Efficacy Komputer terhadap Prestasi Belajar Siswa Paket Keahlian Rekayasa Perangkat Lunak di SMK - Mohammad Mahmudi; Djoko Kustono; Maftuchin Romlie (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This study aims to determine (1) significant influence of students learning motivation with Basic Programming learning outcomes, (2) significant effect of students computer self-efficacy with Basic Programming learning outcomes, (3) Significant differences in Basic Programming learning outcomes between groups of students who are taught with a web centric course are equipped with modules with groups of students who are taught with conventional models with modules. This study employed Nonequievalent Control Group Design with the consideration that the choosing of experimental and control group could not be determined by individual random sampling but it was done through assignment random sampling to the ten graders of software engineering department. Test instrument was used to measure computer self-efficacy and students’ motivation. The data analysis techniques used oneway covariance analysis with two covariates. The results of the study revealed: (1) there is no significant effect of students' learning motivation with Basic Programming learning result, this means less learning motivation in determining the role of treatment and improvement of learning outcomes, (2) there is a significant influence of Self Efficacy Computer students with Basic Programming learning outcomes, and (3) there is a significant difference in Basic Programming learning outcomes between groups of students taught with web centric courses equipped with modules with groups of students taught with conventional learning models equipped with modules.Abstrak: Penelitian ini bertujuan untuk mengetahui (1) pengaruh yang signifikan motivasi belajar siswa dengan hasil belajar Pemrograman Dasar, (2) pengaruh yang signifikan self-efficacy komputer siswa dengan hasil belajar Pemrograman Dasar, dan (3) perbedaan yang signifikan hasil belajar Pemrograman Dasar antara kelompok siswa yang diajar dengan web centric course dilengkapi modul dengan kelompok siswa yang diajar dengan model konvensional dilengkapi modul. Penelitian ini menggunakan rancangan Nonequievalent Control Group Design dengan pertimbangan bahwa dalam penentuan kelompok eksperimen dan kelompok kontrol tidak dapat dilakukan dengan random acak individu, tetapi dilakukan dengan random kelompok (assignment random sampling) yaitu pada kelas X paket keahlian Rekayasa Perangkat Lunak. Teknik analisis data menggunakan analisis covariance satu jalan dengan dua covariate. Hasil penelitian menunjukkan (1) tidak ada pengaruh yang signifikan motivasi belajar siswa dengan hasil belajar Pemrograman Dasar, ini berarti motivasi belajar kurang berperan dalam menentukan pemberian perlakukan dan peningkatan hasil belajar, (2) ada pengaruh yang signifikan Self Efficacy Komputer siswa dengan hasil belajar Pemrograman Dasar, dan (3) ada perbedaan hasil belajar Pemrograman Dasar yang signifikan antara kelompok siswa yang diajar dengan web centric course dilengkapi modul dengan kelompok siswa yang diajar dengan model pembelajaran konvensional dilengkapi modul.